THE INFLUENCE OF HEALTH EDUCATION USING VIDEO MEDIA ON THE KNOWLEDGE AND SKILLS OF PUBLIC WOMEN REGARDING CORRECT BREASTFEEDING TECHNIQUES AT PMB MURNIYATI - Ayu Zahra, Yelsya; Widyastutik, Desy; Prastyoningsih, Aris (Journal of Advanced Nursing and Health Sciences, 2024)
There are many cases where mothers cannot breastfeed well and need help to make the breastfeeding process successful. Fundamental data from health research (RISKESDAS 2021), there are 52.5% or only half of the 2.3 milion infants under the age og six months are reportedly exclusively breastfed in Indonesia, this means a decrease of around 12% from 2019. Providing health education regarding techniques Proper breastfeeding is expected to increase breast milk coverage rates in Indonesia. The goal of this study was to ascertain how health education affected pospartum moms’ knowledge and proficiency with proper breasfeeding procedures at PMB Murniyati. This particular type of research uses preexperimental method with a one group pretest-posttest design model. Gathering of data technique used total sampling, the sample was 30 people. The instruments used were a knowledge questionnaire sheet and a breastfeeding technique skills observation sheet. Data analysis used the Wilcoxon Signed Ranks Test. The outcomes of this research are the impact of health education on understanding and skills of postpartum mothers regarding correct breastfeeding techniques at PMB Murniyati with a difference in pretest and posttest p-values ​​of 0.000 <0.05. The finding that health education has an impact on the abilities and understanding of postpartum mothers regarding correct breastfeeding techniques at PMB Murniyati.